Airplanes with an electric motor - Radek Jurecka (Aviation, 2012)
With the decreasing supply of fossil fuel, we can see more and more attempts to substitute combustion engines with other sources of propulsion. This article deals with the possibility of using alternative sources of energy in aviation. Namely, it describes the possibilities of the advantages and disadvantages of using hydrogen fuel cells in aviation.